2002
DOI: 10.1177/000331970205300503
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Pentoxifylline or Cilostazol to Improve Blood and Plasma Viscosity, Fibrinogen, and Erythrocyte Deformability in Claudication

Abstract: Peripheral artery disease is associated with altered blood rheologic properties, including increased viscosity and decreased red blood cell (RBC) deformability. Pentoxifylline and cilostazol are available therapies for intermittent claudication. Improvement of blood viscosity and erythrocyte deformability have been cited as potential mechanisms of action for pentoxifylline. Cilostazol is a new drug with antiplatelet and vasodilating activity, but the mechanism by which it promotes an improvement in walking is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…[118][119][120] However, a recent study failed to support this hypothesis in blood samples taken from patients with moderate to severe claudication. 121 The beneficial response to pentoxifylline is small in most patients, and the overall data are insufficient to support its widespread use in patients with claudication. 12 Pentoxifylline should be reserved for patients who cannot take cilostazol, have not responded adequately to an exercise program, and/or are not candidates for revascularization procedures or clinical trials.…”
mentioning
confidence: 99%
“…[118][119][120] However, a recent study failed to support this hypothesis in blood samples taken from patients with moderate to severe claudication. 121 The beneficial response to pentoxifylline is small in most patients, and the overall data are insufficient to support its widespread use in patients with claudication. 12 Pentoxifylline should be reserved for patients who cannot take cilostazol, have not responded adequately to an exercise program, and/or are not candidates for revascularization procedures or clinical trials.…”
mentioning
confidence: 99%
“…Haemorrheologiai kezelés a vér és a plazma viszkozitá-sát csökkentő isovolaemiás haemodilutio is. Emellett a thrombosisprofi laxis céljából thrombocytagátló gyógy-szereket (aszpirin, clopidogrel) alkalmazhatunk [1, 2, 3, 4, 5, 6,7,8,9,10,11,12].…”
Section: Eredeti Közleményunclassified
“…Hatására szignifi káns mértékben nő a vörösvérsejtek deformabilitása, csökken a vörösvérsejtek és a thrombocyták aggregabilitása [1, 6,7,8,10,12]. Bár van olyan vizsgálat is, amely a pentoxifi llin kedvező haemorrheologiai hatását nem tudta igazolni [2].…”
Section: Eredeti Közleményunclassified
“…Though the CAPRIE trial demonstrated clopidogrel's superiority to aspirin (acetylsalicyclic acid) in reducing ischemic vascular events in 6452 PAD patients (relative risk reduction 24%), there is no medical evidence to date that clopidogrel relieves the symptoms of intermittent claudication. 6 2…”
Section: Antiplatelet Medicationsmentioning
confidence: 99%
“…However, these purported effects may no longer be valid since a recent investigation revealed no signi cant difference in whole blood viscosity, erythrocyte deformability, or brinogen levels in patients receiving pentoxifylline over a 24-week period of time. 6 Pentoxifylline's mechanism(s) of action may be white blood cellmediated since other articles have documented subsequent changes in the function, 7 adhesion, 8 and cytoskeleton 9 of the leukocyte.…”
Section: Introductionmentioning
confidence: 99%